A series of nano/micro-sized metal–organic frameworks with tunable photoluminescence properties1. Issue 11 (21st March 2015) - Zheng, Yuhua; Liu, Kai; Sun, Xun; Guan, Rengui; Su, Huijuan; You, Hongpeng; Qi, Caixia
<x xml:space="preserve">Abstract</x> Hierarchically assembled nanostructures of lanthanide-based MOFs with tunable emission have been successfully fabricated via a simple method at room temperature.